Mutual Funds in Developing Markets : Addressing Challenges to Growth - World Bank Group (World Bank, Washington, DC, 2015)
This World Bank publication provides an overview of mutual funds in developing countries, outlining their role in the financial sector; the different types of mutual funds; the structure of the mutual fund industry; and the industry’s interdependency with other sectors such as pension funds and insurance companies. The report then outlines the key elements of the legal/regulatory/ taxation framework that typically governs mutual funds and identifies aspects of these frameworks that can drive the growth of mutual funds. Lastly, the report provides an analysis of key market drivers and impediments to mutual fund development. The report builds on five case studies of mutual fund industries in Brazil, Kenya, Morocco, Peru, Turkey, which are provided in the annex.